Regionality in Australian Pinot noir wines: A study on the use of NMR and ICP-MS on commercial wines. (15th March 2021) - Duley, Gavin; Dujourdy, Laurence; Klein, Susanne; Werwein, Anna; Spartz, Christina; Gougeon, Régis D.; Taylor, Dennis K.
Highlights: Wine chemistry is defined in part by terroir (viticultural soil, aspect, & climate) Analytical techniques have been used to characterise wines and to detect wine fraud. We used ICP-MS & NMR to characterise bottled Pinot Noir wines from Australia and NZ. Wines from Australian and NZ regions were somewhat distinguished using ICP-MS. Neither NMR nor ICP-MS successfully distinguished between vintages. Abstract: Wine quality and character are defined in part by the terroir in which the grapes are grown. Metabolomic techniques, such as nuclear magnetic resonance (NMR) spectroscopy and inductively coupled plasma mass spectrometry (ICP-MS), are used to characterise wines and to detect wine fraud in other countries but have not been extensively trialled in Australia. This paper describes the use of ICP-MS and NMR to characterise a selection of Pinot noir wines. Wines from varying terroirs could be somewhat distinguished by their mineral content using principal component analysis (PCA). PCA was able to separate wines by their Australian states more clearly than by region. Metabolomic analysis of the wines using NMR did not find any correlations with climate/daytime temperatures, or region. An analysis of coinertia suggested that the two datasets were not redundant, and it is proposed that ICP-MS data is the most useful for determining regionality.